PINK1/Parkin-Mediated Mitochondrial Autophagy Participates in H2O2-Induced Abnormal Proliferation of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis - Wang G; Chen X; Shao Y; Xu B (Dove Medical Press, 2023)
Gaoyuan Wang,1 Xiaoyu Chen,2 Yubao Shao,2 Bin Xu1 1Department of Orthopaedics, the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of China; 2Department of Histology and Embryology, Anhui Medical University, Hefei, Anhui, People's Republic of ChinaCorrespondence: Bin Xu, Email youchen100@126.comIntroduction: To explore the role of PINK1/Parkin-mediated mitochondrial autophagy in H2O2-induced abnormal proliferation of rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS).Methods: Firstly, we isolated fibroblast like synoviocytes (RA-FLS) from RA patients. H2O2-induced oxidative stress, and NAC (a ROS inhibitor) or FCCP (a mitochondrial autophagy activator) treatment inhibited ROS level or activate mitochondrial autophagy in RA-FLS. MitoSOX Red, JC-1 kit, DCFH-DA kit and CCK8 kit were used to evaluate mitochondrial redox status, mitochondrial membrane potential, intracellular ROS level and cell activity, respectively. Western blot was used to detect the protein expression. The rat model of Freund's complete adjuvant arthritis (AA) was established and treated with NAC and FCCP, respectively. The pathological changes of synovium and the percentage of apoptotic cells in synovium were detected by H&E and TUNEL staining, respectively.Results: We have successfully isolated synovial cells from RA patients. Using 5μM H2O2 to stimulate RA-FLS could induce mitochondrial abnormalities of RA-FLS and inhibit RA-FLS autophagy. FCCP could reverse the effect of H2O2 on RA-FLS cell proliferation and apoptosis. NAC could reverse the effect of H2O2 on PINK1/Parkin. Overexpression of PINK1 or Parkin reversed the effect of H2O2 on RA-FLS mitochondrial autophagy, proliferation and apoptosis. The in vivo experiment results showed that both NAC and FCCP could prevent the pathogenesis of RA, reduce RA-FLS cell viability and increase RA-FLS cell apoptosis.Conclusion: The PINK1/Parkin-mediated mitochondrial autophagy participates in H2O2-induced abnormal proliferation of RA-FLS, and targeting of PINK1/Parkin-mediated mitochondrial autophagy may be the key mechanism in the treatment of RA.Keywords: mitochondrial autophagy, rheumatoid arthritis, PINK1, Parkin